PENINGKATAN KEMAMPUAN MENGGAMBAR RAGAM HIAS GEOMETRIS DENGAN KERTAS LIPSI - Kasim Suharyoso (Universitas Trisakti, 2021)
AbstractThe Increasing of Geometrical Ornaments Drawing Ability with LIPSI Paper Media. The result of the geometrical ornaments drawing in SMPN 2 Gending tend to not indicated the ornamental characteristic. The students had some difficulties to organizing the visual elements into motives, and to developing pattern or repetition into the geometrical ornaments. Therefore, the media to help students to draw is needed. This research aims to describe the application and the increasing of the of geometrical ornaments drawing ability by using LIPSI paper media. This research is a quantitative research, with the Classroom Action Research (CAR) the Hopkins model by two cycles method. In each cycle the research conducted the action of planning, acting, observing, and reflecting. The data obtained through observation, student works, and research notes. There are increasing of the students drawing ability that is indicated through the rise of KKM achievements as much 24,13 % in cycle 1 and 3,46 % from cycle 1 to cycle 2. The increasing from pre-cycle to cycle 2 is 27,59%. The that symmetrical and measured characteristic of LIPSI paper had helped students drawing activities toward significant improvement.Keywords: drawing, geometrical, ornaments, lipsi paper AbstrakPeningkatan Kemampuan Menggambar Ragam Hias Geometris Dengan Kertas LIPSI. Hasil kegiatan menggambar ragam hias geometris di SMPN 2 Gending cenderung belum menampakkan karakteristik ragam hias. Siswa kesulitan dalam mengorganisir bentuk-bentuk geometris menjadi motif dan mengembangkan pola atau pengulangan menjadi ragam hias, sehingga diperlukan media yang dapat membantu dan mempermudah siswa dalam menggambar. Penelitian ini bertujuan mendeskripsikan penerapan dan peningkatan kemampuan menggambar ragam hias geometris menggunakan kertas LIPSI. Penelitian ini adalah penelitian kuantitatif, dengan metode yang dipergunakan adalah Penelitian Tindakan Kelas model Hopkins dengan dua siklus. Pada masing-masing siklus dilakukan kegiatan perencanaan, tindakan, observasi, dan refleksi. Data diperoleh melalui observasi, karya siswa, dan catatan penelitian. Dari penelitian ini diperoleh adanya peningkatan kemampuan menggambar siswa yang ditandai melalui peningkatan pencapaian KKM (Kriteria Ketuntasan Minimal) sebesar 24,13 % pada siklus I, dan 3,46 % dari siklus I ke siklus II. Sehingga apabila dilihat secara keseluruhan peningkatan dari Prasiklus ke Siklus II adalah 27,59 %. Sifat dari kertas LIPSI yang simetris dan terukur membantu aktivitas peserta didik dalam menggambar, sehingga terjadi peningkatan yang signifikan.Kata kunci: menggambar, ragam hias, geometris, kertas lipsi